BORDER proteins protect expression of neighboring genes by promoting 3′ Pol II pausing in plants - Yu, Xuhong; Martin, Pascal G. P.; Michaels, Scott D. (Nature communications, 2019)
Ensuring that one gene’s transcription does not inappropriately affect the expression of its neighbors is a fundamental challenge to gene regulation in a genomic context. In plants, which lack homologs of animal insulator proteins, the mechanisms that prevent transcriptional interference are not well understood. Here we show that BORDER proteins are enriched in intergenic regions and prevent interference between closely spaced genes on the same strand by promoting the 3′ pausing of RNA polymerase II at the upstream gene. In the absence of BORDER proteins, 3′ pausing associated with the upstream gene is reduced and shifts into the promoter region of the downstream gene. This is consistent with a model in which BORDER proteins inhibit transcriptional interference by preventing RNA polymerase from intruding into the promoters of downstream genes. In plants, 3′ Pol II pausing helps prevent transcriptional interference. Here the authors provide evidence that BORDER proteins are enriched in intergenic regions and inhibit transcriptional interference between closely spaced genes by preventing RNA polymerase from intruding into the promoters of nearby downstream genes.